Contemplating historical consciousness : notes from the field - Clark, Anna, 1978-; Peck, Carla L. (Making sense of history, 2018)
The last several decades have witnessed an explosion of new empirical research into representations of the past and the conditions of their production, prompting claims that we have entered a new era in which the past has become more "present" than ever before. Contemplating Historical Consciousness brings together leading historians, ethnographers, and other scholars who give illuminating reflections on the aims, methods, and conceptualization of their own research as well as the successes and failures they have encountered. This rich collective account provides valuable perspectives for current scholars while charting new avenues for future research.